Legacies of multiple disturbances on fruit and seed patterns in Amazonia: Implications for forest functional traits - Brando, Paulo M.; Silvério, Divino; Maracahipes, Leandro; Benzi, Rodrigo; Paolucci, Lucas; Maracahipes‐Santos, Leonardo; Rattis, Ludmila; Macedo, Marcia N.; Balch, Jennifer K. (Ecosphere (Washington, D.C), 2024)
Forest disturbances associated with edge effects, wildfires, and windthrow events have impacted large swaths of the tropics. Defining the levels of forest disturbance that cause ecologically relevant reductions in fruit and seed (FS) production is key to understanding forest resilience to current and future global changes. Here, we tested the hypotheses that: (1) low‐intensity experimental fires alone would cause minor changes in FS production and diversity in a tropical forest, whereas synergistic disturbance effects resulting from edge effects, wildfires, droughts, and blowdowns would drive long‐term reductions in FS diversity and production; and (2) the functional composition of FS in disturbed forests would shift toward tree species with acquisitive strategies. To test these hypotheses, we quantified FS production between 2005 and 2018 in a large‐scale fire experiment in southeast Amazonia. The experimental treatments consisted of three 50‐ha plots: a Control plot, a plot burned annually (B1yr) and a plot burned every three years (B3yr) between 2004 and 2010. These plots were impacted by edge effects, two droughts (2007 and 2010), and a blowdown event in 2012. Our results show that FS production remained relatively high following low‐intensity fires, but declined where fires were most severe (i.e., forest edge of B3yr). The number of species‐producing FS declined sharply when fires co‐occurred with droughts and a windthrow event, and species composition shifted throughout the experiment. Along the edge of both burned plots, the forest community became dominated by species with faster relative growth, thinner leaves, thinner bark, and lower height. We conclude that compounding disturbances changed FS patterns, with a strong effect on species composition and potentially large effects on the next generation of trees. This is largely due to reductions in the diversity of species‐producing FS where fires are severe, causing a shift toward functional traits typically associated with pioneer and generalist species.